A Bowl for a Coin A Commodity History of Japanese Tea - Farris, William (University of Hawai'i Press, 2019)
A Bowl for a Coin is the first book in any language to describe and analyze the history of all Japanese teas. To understand the triumph of the tea plant in Japan, Wayne Farris begins with its cultivation and goes on to describe the myriad ways in which the herb was processed into a palatable beverage. Along the way, he traces the shift in tea's status from exotic gift item from China to its complete nativization in Edo (1603-1868) art and literature and its eventual place on the table of every Japanese household.Farris maintains that tea farming exemplifies the increasing sophistication of Japanese agriculture after 1350, resulting in significant exports of Japanese tea to Euro-American markets. and securing Japan a place among the world's industrialized nations. By 1800, tea had become a central commodity in the formation of a burgeoning consumer society.